(untitled) (Acta Scientiarum. Biological Sciences, 2010)
Periphytic algal community in artificial and natural substratum in a tributary of the Rosana reservoir (Corvo Stream, Paraná State, Brazil). This study evaluated the heterogeneity in periphytic algal community, under the influence of time colonization on artificial substratum. We also examined which abiotic variables most influenced the community in natural and artificial substratum. Egeria najas Planchon was used as natural substratum, and a plastic plant, as artificial. This experiment was carried out in a lateral arm from Rosana Reservoir, formed by Corvo Stream (Paranapanema river basin), in the period from November 21st to December 12nd, 2003, characterized as a warm and rainy period. Changes in species composition were assessed using the similarity indices. 495 taxa were registered in the phycoperiphytic community, distributed in 133 genera and 11 classes. Zygnemaphyceae, Bacillariophyceae, Chlorophyceae and Cyanophyceae presented higher species number, in both substrata. Staurodesmus, Closterium, Staurastrum and Cosmarium (Desmidiales); Gomphonema and Eunotia (Pennales); Characium, Scenedesmus and Desmodesmus (Chlorococcales); Anabaena and Aphanocapsa (Nostocales and Chroococcales, respectively) were the most species-rich genera. The epiphytic community reached the highest species richness in the 15th successional day. Regardless the substratum type, the number of species was probably related to the high concentrations of nutrients (phosphorus and nitrogen).